DETERMINANT OF ISLAMIC BANK SUKUK RATINGS IN INDONESIA - Hutagalung, Muhammad Wandisyah R; Fitria Ana Siregat; Bella Arisha; Ella Zefriani Nasution (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
This study aims to model the factors influencing the Sukuk Ratings at Sharia Commercial Banks in Indonesia by examining key financial variables, including Return on Assets, Return on Equity, Firm Size, Stock Profit, and Debt-to-Equity Ratio. Sukuk ratings provide crucial information for potential investors to assess the risk and return of purchasing specific sukuks. A decline in Sukuk ratings, as observed in this research, could reduce investor interest and increase the risk of default. Sukuk levels, issued by authorized rating agencies, are essential for enabling investors to estimate the risks associated with their investments. Using a quantitative approach with panel data from the PEFINDO website covering three Sharia Commercial Banks from 2021 to 2023, this research applies the Common Effect Model for regression analysis. The findings indicate that variables ROA, ROE, Firm Size, and Stock Profit significantly influence Sukuk Ratings, while DER does not. The coefficient of determination (R²) is 0.77895, indicating that these independent variables explain 77.895% of the variance in sukuk ratings. This model provides valuable insights for investors and regulators in understanding the factors affecting sukuk ratings, thereby aiding better decision-making, enhancing investor confidence, and supporting the growth of the Islamic capital market.